2017
DOI: 10.1089/fpd.2016.2248
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance Profiles ofListeria monocytogenesandListeria innocuaIsolated from Ready-to-Eat Products of Animal Origin in Spain

Abstract: The objective of this work was to investigate the antimicrobial resistance in Listeria spp. isolated from food of animal origin. A total of 50 Listeria strains isolated from meat and dairy products, consisting of 7 Listeria monocytogenes and 43 Listeria innocua strains, were characterized for antimicrobial susceptibility against nine antimicrobials. The strains were screened by real-time PCR for the presence of antimicrobial resistance genes: tet M, tet L, mef A, msr A, erm A, erm B, lnu A, and lnu B. Multidru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 43 publications
6
44
4
Order By: Relevance
“…Zeinali, Jamshidi, Bassami, and Rad () indicated that 52.8%, 44.5%, 41.0%, 25.0%, and 16.7% of 36 L. monocytogenes isolates from fresh chicken carcasses were resistant to erythromycin, tetracycline, clindamycin, trimethoprim, and chloramphenicol. Escolar, Gómez, Del Carmen Rota García, Conchello, and Herrera () reported that 100% and 42.9% of seven L. monocytogenes isolates from RTE meat and dairy products were resistant to clindamycin and ciprofloxacin, respectively. In Egypt, Mohamed, Abdelmonem, and Amin () reported that all 47 L. monocytogenes isolates from frozen vegetables were resistant to amoxicillin, gentamicin, and norfloxacin.…”
Section: Prevalence Of Antibiotic Resistance Among Food Isolates Of Lmentioning
confidence: 99%
See 1 more Smart Citation
“…Zeinali, Jamshidi, Bassami, and Rad () indicated that 52.8%, 44.5%, 41.0%, 25.0%, and 16.7% of 36 L. monocytogenes isolates from fresh chicken carcasses were resistant to erythromycin, tetracycline, clindamycin, trimethoprim, and chloramphenicol. Escolar, Gómez, Del Carmen Rota García, Conchello, and Herrera () reported that 100% and 42.9% of seven L. monocytogenes isolates from RTE meat and dairy products were resistant to clindamycin and ciprofloxacin, respectively. In Egypt, Mohamed, Abdelmonem, and Amin () reported that all 47 L. monocytogenes isolates from frozen vegetables were resistant to amoxicillin, gentamicin, and norfloxacin.…”
Section: Prevalence Of Antibiotic Resistance Among Food Isolates Of Lmentioning
confidence: 99%
“…Six classes of tetracycline resistance genes have been described in Gram‐positive bacteria ( tetK , tetL , tetM , tetO , tetP , and tetS ). However, only tetS , tetM , and tetL have been identified in L. monocytogenes (Charpentier & Courvalin, ; Escolar et al., ; Granier et al., ). It has also been reported that 19 of 38 L. monocytogenes isolates (50%) from dairy farms harbored more than one antibiotic resistance gene sequence.…”
Section: Mechanisms Of Antibiotic Resistance In L Monocytogenesmentioning
confidence: 99%
“…Listeria innocua was used in this study. This bacteria is physiologically very close to the previously mentioned L. monocytogenes, and is frequently found in the same food products, therefore it is often used for experiments [Escolar et al, 2017].…”
Section: Microorganisms and Growth Conditionsmentioning
confidence: 71%
“…The tested organism, L. monocytogenes showed high resistance (100%) to rifampicin, trimethoprim / sulphamethoxazole, linezolid and oxacillin and low resistance (0%) to tetracycline and chloramphenicol (Figure 8). While studies showed that this bacterium has high resistance to rifampicin and oxacillin (Escolar et al, 2017;Kuan et al, 2017), results regarding chloramphenicol vary with other studies. Surprisingly, resistance to ciprofloxacin (87.5%), streptomycin (87.5%) and penicillin G (75%) was found to be high, whereas studies show sensitivity towards these antibiotics (Morvan et al, 2010;Kuan et al, 2017).…”
Section: Antibiotic Susceptibilitymentioning
confidence: 90%
“…monocytogenes are capable of forming biofilms on many abiotic surfaces after short contact times of 20 min (Zadernowska et al, 2017). This formation of biofilms on surfaces like glass and stainless steel gives it the ability to be resistant to harsh chemicals such as detergents and antibiotics; this is because the microbes in the film are embedded in an Extracellular Polymeric Substance (EPS) (Escolar et al, 2017). Drug resistance also arises as a consequence of the misuse of antibiotics and incorrect dosage.…”
Section: Listeriamentioning
confidence: 99%